Pendampingan Pembelajaran Bahasa Inggris Kelas bawah di Sekolah Dasar Islam (SDI) Ulul Albab Badas Kediri - Muhammad Zamroji; Mph. Irfan Fahmi; Zainal Fanani (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
The English learning assistance program for lower-grade students at Ulul Albab Islamic Elementary School (SDI) in Badas, Kediri, aims to enhance students' foundational understanding of a foreign language from an early age. This program addresses the challenge of introducing English at the primary level using an age-appropriate approach. The methods employed involve active, enjoyable, and contextual learning strategies, utilizing interactive media such as songs, games, and storytelling. Additionally, this assistance includes training for classroom teachers to integrate Islamic values into English learning activities. The outcomes indicate improvements in students' learning motivation, basic English skills, and teachers' ability to design and implement creative teaching strategies. This program is expected to serve as a model for effective English learning assistance in Islamic-based schools, particularly at the primary level.